Studi Tentang Pentingnya Analisis Fundamental Saham - Gusni . (Sekolah Tinggi Ilmu Ekonomi STEMBI Bandung, 2015)
Fundamental analysis is the e xamination of the underlying forces that aﬀect the well being of the economy, industry groups and companies. At the economy level, fundamental analysis focuses on economic data to assess the present and future growth of the economy. At the industry level, fundamental analysis focus on the performance of various industries to determine the prospects in the future, and at the company level, fundamental analysis focus on company inancial ratios, management, business concept and company competition. The purpose of fundamental analysis is to estimate the movement of stock prices in the future and proit from the share price movement.